Diversity and Empires : Negotiating Plurality in European Imperial Projects from Early Modernity. - Rose, Sophie. (Taylor & Francis Group, 2023)
Examining diversity as a fundamental reality of empire, this book explores European colonial empires, both terrestrial and maritime, to show how they addressed the questions of how to manage diversity.